2017
DOI: 10.1186/s12885-017-3321-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IKKε by immunohistochemistry in primary breast cancer: association with EGFR expression and absence of lymph node metastasis

Abstract: BackgroundIKKε is an oncogenic kinase that was found amplified and overexpressed in a substantial percentage of human breast cancer cell lines and primary tumors using genomic and gene expression analyses. Molecular studies have provided the rational for a key implication of IKKε in breast cancer cells proliferation and invasiveness through the phosphorylation of several substrates.MethodsHere, we performed immunohistochemical detection of IKKε expression on tissue microarrays constituted of 154 characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Our current data supported these previous findings and interpreted the mechanism of ccl2 inhibition by GoSS. in TnBc cells, the IKBKE gene is expressed in 60% of BC tissue (74) and acts as an oncogene to support cell viability. Furthermore, the up-regulation of IKBKE enhances resistance to anticancer drugs and protects the Bc cells from Tamoxifen-induced apoptosis (75).…”
Section: Discussionmentioning
confidence: 99%
“…Our current data supported these previous findings and interpreted the mechanism of ccl2 inhibition by GoSS. in TnBc cells, the IKBKE gene is expressed in 60% of BC tissue (74) and acts as an oncogene to support cell viability. Furthermore, the up-regulation of IKBKE enhances resistance to anticancer drugs and protects the Bc cells from Tamoxifen-induced apoptosis (75).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the simultaneous overexpression of CCL2 and IKBKE has been established by many studies [ 81 , 82 , 94 ]. In TNBC cells, the IKBKE oncogene is overexpressed in 60% of BC tissues [ 85 , 109 ]. In addition to its main function supporting BC cell viability, upregulated IKBKE increased resistance to antineoplastic therapy by eluding tamoxifen-promoted apoptosis [ 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…In MDA-MB-231 cells, CCL2 gene silencing led to inhibition of CCL2 expression, which—in turn—led to the significant inhibition of tumor growth, cell proliferation, and increased necrosis [ 99 , 114 ]. Hence, the implication of IKBKE in breast carcinoma became a promising prospect for targeted therapies [ 109 ]. The current findings corroborate earlier research and suggest IKBKE repression as the anticipated mechanism of SANG-mediated CCL2 suppression [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…I B kinase subunit epsilon (IKK ), a key component of NF B signalling, has been identified as a breast cancer oncogene [6]. A number of studies have shown that IKK is overexpressed in mammary breast tumours and various human breast cancer cell lines [6,7], and its inhibition reduced the development of primary breast cancer in mice [8]. IKK has also been found to contribute to Tamoxifen resistance in oestrogen receptor positive (ER+) breast cancers [9].…”
Section: Introductionmentioning
confidence: 99%